Expression of insulin‐like growth factor II mRNA‐binding protein 3 in squamous cell carcinomas of the head and neck. (29th May 2012) - Clauditz, T. S.; Wang, C.‐J.; Gontarewicz, A.; Blessmann, M.; Tennstedt, P.; Borgmann, K.; Tribius, S.; Sauter, G.; Dalchow, C.; Knecht, R.; Münscher, A.; Wilczak, W.
<x xml:space="preserve">Abstract</x> J Oral Pathol Med (2013)42: 125–132 Background: Insulin‐like growth factor II mRNA‐binding protein 3 (IMP3) was found overexpressed in various cancer types suggesting its possible role in carcinogenesis. Analysis of IMP3 expression in head and neck squamous cell carcinomas (HNSCC) is rare so that we evaluated it using tissue microarray method. Method: Immunohistochemical analysis of IMP3 was performed on samples from over 400 patients. The expression was measured semiquantitative, subsequently divided into four categories (negative, weak, medium, or strong) and correlated with several available clinicopathologic parameters. Results: For HNSCC, positive IMP3 expression was observed in patients with all tumor stages (pT1–4) and nodal stages (pN0–3), showing also significant statistical correlation (P = 0.023 and P = 0.0013, respectively). No further correlations were found. Separate analysis according to tumor localization (oral cavity, oropharyngeal, and laryngeal) showed a significant correlation of positive IMP3 expression and overall survival (P = 0.038) only in patients with tumors of the oral cavity. Multivariate analysis showed IMP3 as an independent predictive marker for oral squamous cell carcinomas (OSCC). Conclusion: Insulin‐like growth factor II mRNA‐binding protein 3 (IMP3) expression might be used as an independent prognostic factor in the subgroup of OSCC.